17th Century Town Administration and Judiciary of Koprivnica, a Free Royal Borough - Petrić, Hrvoje (Array, 2008)
In the late 16th century, Koprivnica had around five hundred inhabitants (military personnel included). In that period, the entire population lived within the fortification walls, that had been built in the second half of the 16th century. After the Žitva truce, a process of intensive re-population took part. All available empty space was being taken by new settlements and buildings inside the fortification.